Anticancer and antimetastatic effects of cordycepin, an active component of Cordyceps sinensis - Kazuki Nakamura; Kazumasa Shinozuka; Noriko Yoshikawa (Elsevier, 2015)
Cordyceps sinensis, a fungus that parasitizes on the larva of Lepidoptera, has been used as a valued traditional Chinese medicine. We investigated the effects of water extracts of Cordyceps sinensis (WECS), and particularly focused on its anticancer and antimetastatic actions. Based on in vitro studies, we report that WECS showed an anticancer action, and this action was antagonized by an adenosine A3 receptor antagonist. Moreover, this anticancer action of WECS was promoted by an adenosine deaminase inhibitor. These results suggest that one of the components of WECS with an anticancer action might be an adenosine or its derivatives. Therefore, we focused on cordycepin (3'-deoxyadenosine) as one of the active ingredients of WECS. According to our experiments, cordycepin showed an anticancer effect through the stimulation of adenosine A3 receptor, followed by glycogen synthase kinase (GSK)-3β activation and cyclin D1 suppression. Cordycepin also showed an antimetastatic action through inhibiting platelet aggregation induced by cancer cells and suppressing the invasiveness of cancer cells via inhibiting the activity of matrix metalloproteinase (MMP)-2 and MMP-9, and accelerating the secretion of tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 from cancer cells. In conclusion, cordycepin, an active component of WECS, might be a candidate anticancer and antimetastatic agent.